Unconscious Thinking, Feeling and Behavior Towards Products and Brands: Introduction to a Journal of Brand Management Special Issue - Woodside, Arch; Brasel, S. (Palgrave Macmillan, 2011)
This introduction reviews the motivating forces behind this issue, exploring the role of nonconscious consumer behavior in branding environments. The article establishes a foundation of unconscious research in psychology and consumer behavior, and then provides an introduction to the four articles that follow. The article concludes with a call to adopt an inclusive interpretive-positivistic stance to the study of unconscious consumer-brand behavior, attitudes and beliefs.